A Psycholingustics Study Of Dyslexia On The Conflict Of The Main Character In Taare Zameen Par Movie - Dewi, Nova Purnama (Jurnal Ilmiah Mahasiswa Pendidikan [JIMEDU], 2021)
This research discussed learning disabilities as disabilities in reading, writing, and arithmetic. It related to childrens conflict about learning disabilities contained in the Indian movie by Amiir Khan entitled TaareZameen Par. The purpose of this research was to explained, the impact of the conflict of dyslexia in the main character of TaareZameen Par movie, the kinds of dyslexia in the main character of TaareZameen Par movie. Researchers used qualitative methods, and descriptive technique to describe and analyze the data. Through collecting all the data generated from TaareZameen Par movie is taken from , such as script, and the story of the movie, and then relating them to the main character. Based on data analysis which is divided into 90 scenes, but only 12 scenes that can be the data. It was there were the kinds of dyslexia that happen to Ishaan. They were directional dyslexia (2 cases), primary dyslexia (3 cases), and phonological (auditory) dyslexia (4 cases). In the The impact of the conflict by the main character (3cases).